Competitive interactions in plant-parasitic nematode communities affecting organic vegetable cropping systems. (September 2020) - Mateille, Thierry; Tavoillot, Johannes; Goillon, Claire; Pares, Laure; Lefèvre, Amélie; Védie, Hélène; Navarrete, Mireille; Palloix, Alain; Sage-Palloix, Anne-Marie; Castagnone-Sereno, Philippe; Fazari, Ariane; Marteu, Nathalie; et al.
Abstract: Plant-parasitic nematodes (PPN) are detected everywhere as mixed-species communities. Most non-chemical control strategies of PPN only target some species, thus raising questions about the consequences that this specificity may have on the residual community. In this respect, the long-term ecological sustainability of such strategies is challenged. In order to evaluate the impacts of agronomical practices on PPN communities, two four-year experiments that differed by the presence or absence of root-knot nematodes (RKN - Meloidogyne spp.) were carried out under cold shelters in the south of France, under native field conditions of vegetable cropping systems that included a nematicidal sorghum green manure and a pepper variety carrying a RKN resistance gene. At the site with RKN, RKN populations developed on susceptible vegetables. They were controlled by the green manure but not by the R-pepper, and were also vulnerable to low soil temperatures. At the site without RKN, Paratylenchidae populations developed on susceptible vegetables, but were controlled by both the green manure and the R-pepper, and not by low temperatures. At each site, populations of Telotylenchidae exhibited dynamics suggesting competition with RKN or Paratylenchidae. Hypotheses about competition models are discussed according to the specific life traits of the PPN involved, including ecto- vs. endoparasitism and sedentary vs . free-living behaviour, and to the antagonist mechanisms of the cover and resistant crops that must be introduced in vegetable cropping systems. Highlights: Plant-parasitic nematodes (PPN) occur everywhere as mixed-species communities. Practices introduced into vegetable cropping systems impact diversity balances. Endoparasites are more affected by the plant susceptibility than ectoparasites. Ectoparasites are excluded by hierarchical competition with endoparasites. Competition within ectoparasitic species appears to be more cyclic.